Animisms. From Africa to First Nations, thinking decolonization with the writers - (:unkn) unknown (My University, 2018)
This thesis proposes a comparative reflection between the literatures of the First Nations of Quebec and those of sub-Saharan Africa and Afro-descendants and more specifically the poetry of Natasha Kanapé Fontaine, Rita Mestokosho and Josephine Bacon, as well as some of the novels of Léonora Miano and Sami Tchak. The texts of these Innu, Franco-Cameroonian and Togolese poets and writers are based on the notion of animism. By means of literary referents, anthropological studies and Aboriginal studies, this work therefore questions the presence of animism in the practice of writing and questions its decolonial scope. This reflection is also built from fieldworks, by taking into account the promotion of the experiential knowledge advocated by Aboriginal studies. Building on what the researcher Renate Eigenbrod calls "narrative scholarship", namely the alternation between theory and narration, this thesis aims to think of the animist way of being in the world as an epistemology.Through a two-step thought, this work highlights the different effects of colonization on animism as a way of being in the world, as well as its decolonial dynamics through the prism of their literary representation and incarnation. The first chapter analyzes the objectification strategies of animism carried by the colonial policies. The second chapter focuses on the salient characteristics of the literary representation of animism. The question of the relation to the territory and the its inherent notion of sovereignty are discussed in chapter three. Unlike the mechanics of assignment and oppression, our aim is then to reflect on the dynamics of emancipation carried by animism within the texts of our corpus. Chapter four analyzes issues related to the notion of Subject from a decolonial perspective. Then, this is the resistant potentiality of animism as relational ontology which is questioned in chapter five. Finally, chapter six theorizes its practical dimension and its constitu
Keywords: African Research